Pluralism and free competition in the television and radio broadcasting market: the Chilean case - Anguita Ramírez, Pedro (2019)
The study analyzes the constitutional and legal regime applicable to the market of social media in Chile subject to state concession and the decisions made by the entities in charge of ensuring free competition in sales and acquisition operations. The research, according to the evidence obtained, highlights in its conclusions, the insufficiency of said institutionality in the adequate regulation of a market especially relevant for the exercise of freedom of expression in the context of a democratic society.